Persepsi Terhadap Ekspresi Emosi Orang Tua dengan Risiko Terjadinya Problem Mental pada Remaja - Tri Kurniati Ambarini; Nurul Hartini; Inas Ngesti Pribadi; Lailatul Muniroh (Jurnal Ners, 2026)
Emotional expression (EE) is an important indicator for predicting the emergence of mental disorders. EE represents several key dimensions of interpersonal relationships and is commonly classified within families into two major components: critical comments (CC) and emotional over-involvement (EOI) (Nurtantri, 2005). Beyond its predictive capacity for the onset of psychological or psychiatric disturbances, EE also plays a crucial role in preventing relapse among individuals with a history of mental illness. Mapping patterns of emotional expression within families particularly among parents of adolescents with an at-risk mental state (ARMS) is therefore essential for preventive efforts aimed at reducing the likelihood of developing psychological or psychiatric disorders. This study aims to examine the relationship between parental EE patterns and ARMS among adolescents in Surabaya. Using a survey method involving 78 respondents, Pearson’s correlation test revealed a correlation coefficient of r = 0.495 between perceptions of EE and ARMS, indicating that the research hypothesis is supported. The findings demonstrate a positive relationship between perceived EE and ARMS, meaning that higher levels of perceived EE are associated with a greater risk of psychosis.